The Effect of Greenwashing and Eco-Label on the Purchase of Circular Packaging of Environmentally Friendly Skincare Products with Environmental Concern as the Mediation - Padma, Hilda Carissa Putu; Sugandini, Dyah (Journal of Management and Business Environment (JMBE), 2025)
This study explores the impact of greenwashing and eco-label on the purchase of environmentally friendly packaging (purchasing circular packaging) with the mediating role of environmental concern. This is trigered by the threat of skincare and cosmetic waste that continues to increase. Research data were collected through questionnaires to 204 students in Yogyakarta selected using the purposive sampling technique, measured using a Likert scale and analyzed using the PLS method through the Smart PLS 4.1 application. The results of the study showed that: greenwashing has very little negative but insignificant influence on purchasing circular packaging and on environmental concern. Eco-label has a positive and significant influence on purchasing circular packaging and environmental concern. Environmental concern has a positive and significant influence on purchasing circular packaging and is able to mediate the relationship between the influence of greenwashing on purchasing circular packaging negatively and significantly. Environmental concern is able to mediate the relationship between eco-label on purchasing circular packaging positively and significantly. For companies, transparency is expected regarding sustainable and truly environmentally green products.